Islamic Emotional Intelligence Leaders in Conflict Management - Uswatun Khasanah (Al-Hayat: Journal of Islamic Education, 2022)
This study aims to describe how the principal in overcoming or controlling conflicts that occur in the Muhammadiyah Delanggu Vocational High School Klaten, Central Java, Indonesia, is by using Islamic emotional intelligence. This research is a case study using a qualitative approach. The subject of this research is the Principal of the Muhammadiyah Delanggu Vocational High School (SMK) Klaten, Central Java, Indonesia. This study indicates that the principle of controlling conflict by using his emotional intelligence is quite good. This is illustrated by the way the school principal solves existing problems by controlling his emotions so that he does not arbitrarily decide cases that occur, but by holding the collegial collective principle and being able to recognize other people's emotions (empathy) by respecting the feelings of his subordinates not to reprimand them, directly on the spot but by way of deliberation first. This aims to maintain the institution's good name so that neither party gains nor loses. Thus the research findings in this study are to make conflict an opportunity to advance Islamic educational institutions (conflict resolution).